Encourage The Boycott Of Using Fossil Fuels and The Privileges Transition To Green Energy - Otamirzaev Oybek, (International Journal of Human Capital and Innovative Management, 2024)
Today, the environmental crises and problems occurring in different continents of the world are equal concern to the population of all countries. Especially in the current environment, which is undermining ecological stability due to climate change and other natural and anthropogenic influences, it is extremely important to preserve the biological resources that are important for the present and future of humanity. Mineral resources are important in ensuring the economic and even political stability of countries. They are the main element that produces raw materials or energy in certain areas and ensures the stability of countries. Mineral resources are divided into two types. These are recoverable and non-recoverable (or take a long time to recover). The creation of energy sources is based on the use of non-renewable underground resources. At this point, the world community is gradually limiting the use of fossil fuels and carrying out practical work step by step to create green energy sources. So what made him do it?